Conservation and improvement for the production of meat type quail in Bangladesh - Ali, Md Yousuf; Faruque, Shakila; Bhuyian, AKH Fazlul Haque; Joy, Ziaul Faruque; Rabbani, Md Ataul Goni (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The present study was conducted with the aim to develop a meat type quail genotype for our existing farming system. A total of 1866 quails from four genotypes namely Japanese, White, Black and Brown were used in the study for this purpose. The parent males and females were maintained in cages for single pair mating through close breeding system for producing each generation. Eggs were hatched in a batch for producing third generation (G3). Egg weight were significantly influenced (p<0.05) by genotype. Highest egg weight was found in White (11.60±0.42) genotype followed by Japanese (10.35±0.30), Brown (10.30±0.42) and Black (9.78±0.65) quail genotypes. The highest hatchability of incubated eggs was found in Japanese (71.01%) genotype and lowest in Black (31.03%). White genotype of quail is significantly better for egg weight, chick weight and chick: egg ratio than that of their counterparts. Significantly higher body weight was found in Black (131.90 ± 1.24) genotype followed by White (131.86 ± 0.76), Brown (128.35 ±0.78) and Japanese (112.57 ± 0.53) quail genotype at different periods of age. Egg production was found significantly (p<0.001) differed by genotypes. Black genotype was found highest (97.31±1.05%) while White genotype was found lowest (84.23±0.67%) performer in terms of egg production. It was concluded that the Black quail genotype can be used for meat type quail development in the country for its higher body weight and egg production. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 425-428